Hacia una nueva función de la marca: Creación de activos intangibles mediante asociaciones en la mente del consumidor basada en la Identidad de Marca y Valor percibido de Marca, y su aplicación en las disciplinas de la Propiedad Industrial y Competencia D - Castro Angulo, Alejandro (2025)
This article identifies a new brand function: the creation of intangible assets through associations. It develops branding concepts from a marketing perspective and traces the brand’s evolution from company -centered value to a competitive consumer- focused asset. The analysis focuses on how this function applies within Industrial Property and Unfair Competition law, particularly through Articles 137 and 155 of Decision 486. The feasibility of applying Article 137 is affirmed, while Article 6 of Legislative Decree N° 1044 is considered insufficient for protection. Creating intangible assets via associations strengthens brand equity and supports premium pricing, though its full implementation remains a challenge for legal frameworks in these areas.